Clinico-pathological Study of Enteric Fever at Rapti Academy of Health Sciences, Ghorahi, Dang, Nepal - Jha, Krishna Kumar; Regmi, Dipesh (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: The most typical cause of fever in developing nations is enteric fever. Because the complications are extremely severe, an early diagnosis is essential. Early diagnosis can improve the patient's chance of being cured. Thus, the objective of our study was to compare between blood culture, IgG and IgM method. MATERIALS AND METHODS: This study was conducted among 240 clinically suspected cases of enteric fever from 17th February 2019 to 17th May 2019 at Rapti academic of health science, Dang. We have done first Blood culture was performed and IgG and IgM method were used to detect enteric fever for same sample. RESULTS: Out of 240 patients, 112 of the 240 cases were men and 128 were women. Blood culture testing revealed 72 positive samples, or 30%, and IgG and IgM testing revealed 64 positive cases, or 26.66%, for the same cases. Therefore, our investigation demonstrated that the blood culture method is equally as successful as the IgG and IgM method. CONCLUSIONS: The study concludes that he blood culture IgG and IgM methods are equally effective. There are not always blood culture settings accessible in developing countries like Nepal. Therefore, IgG and IgM methods are preferable.